What are the common challenges to adopting a zero trust network model? (O'Reilly, 2017)
"Once you know what a zero trust network is, and what the advantages and disadvantages of moving to this model are, the next step is to understand some of the common challenges that you will face in implementing zero trust as a security model. Evan Gilman and Doug Barth discuss these challenges, and give suggestions on how to overcome them. You will get tips on why to involve more than just your security team, why implementing policy as code is important, understanding why you should evaluate policies for their impact and value, and the overall scale of change involved in moving from a perimeter model to a zero trust model."--Resource description page